2016
DOI: 10.1590/0100-5405/2075
|View full text |Cite
|
Sign up to set email alerts
|

Anthesis, the infectious process and disease progress curves for fusarium head blight in wheat

Abstract: Fusarium head blight of wheat (Triticum aestivum), caused by the fungus Gibberella zeae, is a floral infecting disease that causes quantitative and qualitative losses to winter cereals. In Brazil, the sanitary situation of wheat has led to research in order to develop strategies for sustainable production, even under adverse weather conditions. To increase the knowledge of the relationship among the presence of anthesis, the infectious process, the disease progress and the saprophytic fungi present in wheat an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 14 publications
1
18
1
Order By: Relevance
“…However, these diseases seem not to be related to the severity of fusarium head blight in spikes. Leaf disease control is known to be independent of fusarium head blight control (24). The results found in the current study, in general, show that foliar disease control does not statistically reduce fusarium head blight symptoms, compared to absolute control.…”
Section: Discussioncontrasting
confidence: 64%
“…However, these diseases seem not to be related to the severity of fusarium head blight in spikes. Leaf disease control is known to be independent of fusarium head blight control (24). The results found in the current study, in general, show that foliar disease control does not statistically reduce fusarium head blight symptoms, compared to absolute control.…”
Section: Discussioncontrasting
confidence: 64%
“…Thus, cultivar response and fungicides with appropriate spray frequencies and subsequent variation in FHB pressure could be responsible for comparative yield advantages, which were obtained per treatment across the locations, along with other factors. As reported by Mesterh azy et al ( ), McMullen et al (2008, Wegulo et al (2011), Willyerd et al (2012), and Reis et al (2016, integration of cultivar resistance and fungicide applications with frequent spraying of fungicide reduces FHB pressure and increased yield and yield-related attributes than the unsprayed control plots.…”
Section: Discussionmentioning
confidence: 74%
“…As mentioned by the previous researchers, a plant disease was strongly associated with losses of growth and yield-related traits of the crop in every portion of disease progression (Campbell and Madden, 1990;Cook et al, 1999;Agrios, 2005). Likewise, in the integration of host resistance and fungicide application with frequent spray evaluation for FHB studies, Gilbert and Haber (2013), Wegulo et al (2015), Reis et al (2016), andShude et al (2020) reported variable levels of relationships between the studied parameters in various parts of the world.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…genus and, in South America, Fusarium graminearum (teleomorph Giberella zeae) and Fusarium culmorum (teleomorph unknown) are the prevalent species (Arrúa et al 2015). Fusarium head blight infection is largely dependent on environmental conditions, with optimal temperatures of 20-30 ºC and humidity of 80 %, for periods of 48-60 hours during the anthesis, which is the most vulnerable period of the crop (Siou et al 2014, Reis et al 2016.…”
Section: Avaliação Da Resistência De Genótipos De Trigo à Fusariose Nmentioning
confidence: 99%